CD44: a cancer stem cell marker and therapeutic target in leukemia treatment - Wu, Shuang; Tan, Yicheng; Li, Fanfan; Han, Yixiang; Zhang, Shenghui; Lin, Xiaofei (Frontiers in Immunology, 2024)
CD44 is a ubiquitous leukocyte adhesion molecule involved in cell-cell interaction, cell adhesion, migration, homing and differentiation. CD44 can mediate the interaction between leukemic stem cells and the surrounding extracellular matrix, thereby inducing a cascade of signaling pathways to regulate their various behaviors. In this review, we focus on the impact of CD44s/CD44v as biomarkers in leukemia development and discuss the current research and prospects for CD44-related interventions in clinical application.